Schema therapy for violent PD offenders: a randomized clinical trial. Issue 1 (15th June 2021) - Bernstein, David P.; Keulen-de Vos, Marije; Clercx, Maartje; de Vogel, Vivienne; Kersten, Gertruda C. M.; Lancel, Marike; Jonkers, Philip P.; Bogaerts, Stefan; Slaats, Mariëtte; Broers, Nick J.; Deenen, Thomas A. M.; Arntz, Arnoud
Abstract: Background: Violent criminal offenders with personality disorders (PD's) can cause immense harm, but are often deemed untreatable. This study aimed to conduct a randomized clinical trial to test the effectiveness of long-term psychotherapy for rehabilitating offenders with PDs. Methods: We compared schema therapy (ST), an evidence-based psychotherapy for PDs, to treatment-as-usual (TAU) at eight high-security forensic hospitals in the Netherlands. Patients in both conditions received multiple treatment modalities and differed only in the individual, study-specific therapy they received. One-hundred-three male offenders with antisocial, narcissistic, borderline, or paranoid PDs, or Cluster B PD-not-otherwise-specified, were assigned to 3 years of ST or TAU and assessed every 6 months. Primary outcomes were rehabilitation, involving gradual reintegration into the community, and PD symptoms. Results: Patients in both conditions showed moderate to large improvements in outcomes. ST was superior to TAU on both primary outcomes – rehabilitation (i.e. attaining supervised and unsupervised leave) and PD symptoms – and six of nine secondary outcomes, with small to moderate advantages over TAU. ST patients moved more rapidly through rehabilitation (supervised leave, treatment*time: F (5308) = 9.40, p < 0.001; unsupervised leave, treatment*time: F (5472) = 3.45, p = 0.004), and showed faster improvements on PD scales (treatment*time: t (1387) = −2.85, p = 0.005). Conclusions: These findings contradict pessimistic views on the treatability of violent offenders with PDs, and support the effectiveness of long-term psychotherapy for rehabilitating these patients, facilitating their re-entry into the community.